Peningkatan Keterampilan Menulis Teks Prosedur Menggunakan Model Proyek Based Learning dengan Media Animasi pada Siswa Kelas Xi TKJ-2 SMK Negeri 2 Karang Baru - Ash Habibi (Medan Resource Center, 2022)
This study used a type of Classroom Action Research (PTK). (Classroom Action Research). The subject of this study is the skill of writing procedure texts in grade students of SMKN 2 Karang Baru, . The source of this research data is students of SMKN 2 Karang Baru, . The number of students in one class selected as respondents was 20 students. Data collection techniques use test techniques and non-test techniques. Data analysis techniques are carried out in two ways, namely quantitative data analysis techniques and quality data analysis techniques. Results The learning process of writing procedures with a project bassed learning model assisted by animated video media as a whole went well. This is evidenced by the results of observations that show an increase from cycle I to cycle II. The results of changes in religious and social attitudes of the students of SMKN 2 Karang Baru class, experienced a change in a positive direction. Most of the students showed a good attitude of behavior from cycle I to cycle II in learning to write procedures with a project-based learning model with animated video media. The results of the procedure writing skills test with the project bassed learning model assisted by animated video media in grade students of SMKN 2 Karang Baru, experienced an increase from cycle I to cycle II.